2018
DOI: 10.22149/teee.v3i1.118
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical analysis of the efficiency of a V2G wireless charger for Electric Vehicles

Abstract: V2G (Vehicle-to-grid) technology will report important benefits for the operation and safety of the grid. In order to facilitate the expansion of the V2G technology in a future, it is recommended to offer the drivers with easy to use methods to charge and discharge their EV batteries. In this sense, wireless chargers are expected to play a relevant role in the future electrical networks as it reduces the users intervention. The development of this kind of system is still open to improve them in terms of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In this approach, the flow of the active power is easily adjusted, and the expected efficiency can be computed as in [58]. There must be coordination between the power converters to set the configuration in both controllers.…”
Section: Activation Of the Power Convertersmentioning
confidence: 99%
“…In this approach, the flow of the active power is easily adjusted, and the expected efficiency can be computed as in [58]. There must be coordination between the power converters to set the configuration in both controllers.…”
Section: Activation Of the Power Convertersmentioning
confidence: 99%
“…Some of the prospects of the study is the optimization of the system to allow load balancing, filling and peak shaving [10,11]. A mathematical model for the estimation of the charge and discharge efficiency in an EV bidirectional ICPT wireless charger was presented [12]; the WPT system was characterized and validated experimentally using a 3.7 kW prototype. It was suggested that V2G systems need improvement in operational mechanism, compliance and control.…”
Section: Introductionmentioning
confidence: 99%